Inadvertent discrimination in medical research - Geis, Sally B. (Journal of religion and health, 1990)
Most institutional decision makers profess commitment to ethical or religious principles that judge discrimination to be repugnant and immoral. They also acknowledge the existence of racism, sexism, and elitism in American society but believe their own decisions are free of such discrimination. The elimination of institutional discrimination will occur only when decision makers can engage in critical analysis of the frames of reference and patterns of thinking out of which their decisions develop. Individuals who are not decision makers but who are committed to the elimination of discrimination must understand and influence the patterns of thinking used by those in power. This case study, initiated by a black woman psychiatrist and a white woman sociologist, illustrates the need for such understanding. The description of this experience with decision making in academic medical research is illustrative of the larger societal issue.